TELE-PAY A SUBSTITUTE OF CONVENTIONAL BANKING: A CONCEPTUAL STUDY - Rehman, Muhammad Shujah; Salam, Zarina Abdul; Tareq, Mohammad Ali (PEOPLE: International Journal of Social Sciences, 2016)
In modern era technology advancement make life easier and quicker. As adoption of technology becomes the essential part of every organization, same is happening in banking industry. Currently, technology acceptance is one of the core issue discussed in banks executive management meetings. The biggest challenge in the service industry is to provide the financial services to those who don’t have access to it. This study focuses to enhance the solution for delivering financial services as a tele-pay through integration rather than direct branch banking. Telecom and bank collaboration solve the problem of providing basic financial services to those who do not have access the services either due to their remoteness or inaccessibility. Tele-pay is considered as mobile payment services provided through telecom companies. Using Technology acceptance model (TAM) we have investigated four factors which are important for adoption of mobile payment by the customers i.e; trust, accessibility, perceived ease of use and perceived usefulness. Technology acceptance model (TAM) is widely used to analyze these factorsinfluence on adoption of mobile payment. Studies have considered compatibility, self efficacy and social influence affecting mobile payment adoption and trust, accessibility, perceived ease of use and perceived usefulness were found to be more relevant for customer acceptance. These indicators are used to investigate in the context of Pakistan to enhance mobile payment acceptance. The implication of this study for both telecom and banking industry is to further explore the ways for ease of adoption for mobile payment services among mass people.